The phenomenology of colonialism: Exploring perspectives of social work graduates in the African university - Makhanya, Thembelihle (Critical Studies in Teaching and Learning, 2023)
This article unpacks African students’ understanding of colonialism in higher education through the narratives of social work graduates who attended a university located in KwaZulu-Natal. The research study is inspired by the 2015/2016 #RhodesMustFall and #FeesMustFall movements, which suggested a need to explore students’ views regarding colonialism in higher education. The data was collected through group interviews with twenty-two graduates. Framed within the Afrocentric theoretical framework and the phenomenology paradigm, the article explores the concept of colonialism in higher education and beyond. Participants’ thinking on colonialism in higher education and beyond was not homogenous and some key themes emerged. Participants described colonialism in higher education as a product of the past where white supremacy and European domination served to oppress and alienate Africans from their identities and the university space. They also saw universities as spaces where Eurocentric indoctrination occurred, supported by the misrepresentation and marginalisation of Africans, which led to further isolation of African identities of self.